2021
DOI: 10.1097/md.0000000000026732
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of disease-related risk factors for central venous catheter-related symptomatic thrombosis in intensive care unit inpatients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The risk factors for thrombotic occlusion are various, and organic factors include endothelial damage, stasis of venous flow, and/or an underlying prothrombotic state 12 . Other factors associated with the development of thrombotic occlusion in cancer patients include the type of central venous catheter, insertion in the subclavian vein, left-sided insertion, longer duration of catheter insertion, catheter-to-vein ratio, professional expertise, and optimal routine care 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors for thrombotic occlusion are various, and organic factors include endothelial damage, stasis of venous flow, and/or an underlying prothrombotic state 12 . Other factors associated with the development of thrombotic occlusion in cancer patients include the type of central venous catheter, insertion in the subclavian vein, left-sided insertion, longer duration of catheter insertion, catheter-to-vein ratio, professional expertise, and optimal routine care 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on prospectively collected data on 1586 patients with 96 CRT events (6.1%), our study has shown that the insertion site of the catheter, size of the catheter, and indwelling time are significant risk factors for thrombotic occlusion. The risk factors for thrombotic occlusion are various, and organic factors include endothelial damage, stasis of venous flow, and/or an underlying prothrombotic state 12 . Other factors associated with the development of thrombotic occlusion in cancer patients include the type of central venous catheter, insertion in the subclavian vein, left-sided insertion, longer duration of catheter insertion, catheter-to-vein ratio, professional expertise, and optimal routine care 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of catheter-related venous thromboembolism (VTE) varies widely, from 9.5 per 1000 catheter days in critically ill patients [7] to 5-13.5% in oncology and hematological patients [8,9].…”
Section: Introductionmentioning
confidence: 99%